The role of condensed tannins towards ovine nematodes and their consequences on host performance - Athanasiadou, Spiridoula Georgiou (The University of Edinburgh, 2001)
The aim of this thesis was to investigate the two hypotheses that have been put forward to account for the reduction in the level of parasitism observed in sheep that consume condensed tannins. For this purpose in vitro (larval development/ viability assay) and in vivo experiments were performed. In the first two experiments, a model condensed tannin extract (Quebracho) was given as a drench to parasitised sheep to test for the direct effect of condensed tannins towards established adult nematodes. Experiment 1 aimed to provide evidence for a direct anthlemintic effect of condensed tannins towards an established Trichostrongylus colubriformis population. For this purpose the extract was administered to sheep four weeks after their initial infection. There was clear evidence for a direct anthelmintic effect of condensed tannins towards adult T. colubriformis, as demonstrated by reduced faecal egg counts and worm burdens. As T.colubriformis is an intestinal ovine nematode, the susceptibility of other intestinal and abomasal ovine nematodes to condensed tannins was investigated in vitro and in vivo.

In vitro larval development/viability assays were performed to test for the effects o f different concentrations of Quebracho extract on pre-parasitic larval stages of one intestinal (Trichostrongylus vitrinus) and two abomasal nematodes (Teladorsagia circumcincta and Haemonchus contortus) (Experiment 2a). The results from these assays showed that larvae from all species were able to develop to infective larvae, irrespectively the concentration of Quebracho extract. Flowever, the viability of infective larvae of all species decreased, as the concentration of condensed tannins increased. Concurrently, Experiment 2b was designed to test whether condensed tannins had a direct anthelmintic effect towards adult populations of either T. circumcincta or H. contortus, or towards a mixed intestinal population of Nematodirus battus and T.colubriformis. Both ovine intestinal species were susceptible to the presence of condensed tannins in the gastrointestinal tract of sheep, as demonstrated from reduced faecal egg counts and worm burdens. On the other hand, neither the fecundity nor the worm burden of abomasal nematodes was affected by the presence of Quebracho extract. The absence of a direct effect against abomasal species could have been due to either speciesspecific differences in susceptibility or organ-specific physico-chemical differences.

In Experiments 3 and 4, Quebracho extract was incorporated in both low and high protein diets of parasitised sheep, in order to test for direct and indirect effects of condensed tannins during the establishment and the maintenance of an intestinal nematode infection. Experiment 3 tested whether the consumption of high protein foods supplemented with Quebracho extract fed as an allowance of the liveweight would reduce the level of intestinal parasitism in sheep and consequently improve their performance. Although the level of the parasitic infection, as judged by faecal egg counts and worm burdens, was reduced in sheep offered the foods supplemented with Quebracho extract, their performance was not improved. It was proposed that this could have been due to an anti-nutritional effect of condensed tannin on food digestibility, which sheep were not able to overcome because of the restricted feeding regime. The final experiment of the thesis (Experiment 4) aimed to test whether the ad libitum consumption of either low or high protein foods supplemented with Quebracho extract would reduce the level of intestinal parasitism and achieve improved performance. It was hypothesised that ad libitum intake would enable sheep to eat to the extent required to overcome antinutritional effects of condensed tannins upon digestibility. For this purpose, the Quebracho extract was added in the foods of parasitised sheep at the same level as in experiment 3. The level of parasitism was reduced in sheep offered foods supplemented with Quebracho extract only during the initial establishment of the infection, as indicated by reduced faecal egg counts. Although the digestibility of foods was not affected by the addition of Quebracho extract in the foods, the performance of sheep was not improved. It was proposed that sheep fed ad libitum might require higher concentrations of Quebracho extract in their foods to reduce the level of parasitism, compared to sheep fed restrictedly, as a result of reduced retention time of condensed tannins in the gastrointestinal tract.

The outcomes of the above experiments are brought together and the potential applications of condensed tannins as an alternative to control gastrointestinal parasitic infections in sheep are considered in the General Discussion.